Cancer mortality in 2020 and its trend analysis in Inner Mongolia during four time periods from 1973 to 2020 - Hou, Ruili; Mu, Zhiqi; Kang, Weiwei; Liu, Zhengran; Na, Buqi; Niu, Wenliang (Frontiers in Oncology, 2023)
Cancer is one of the leading causes of mortality in China and is responsible for placing a major burden on its economic system. Inner Mongolia is located close to the northern border of China and spans more than 2,400 km from east to west. It has a total area of 1,183,000 km2, which accounts for about one-third of the total area of the country. Its ethnic demographics are complex and unique. We were interested in understanding whether these situations lead to a higher mortality rate for certain types of cancer, which was the motivation behind our research. This study aims to estimate cancer mortality in Inner Mongolia, its burden, and its trend over a 60-year time span. We compiled data pertaining to cancer in Inner Mongolia, obtained from the three national causes of death sample surveys. In addition, we obtained data pertaining to cancer mortality rates from the cause of death surveillance system in Inner Mongolia in the year 2020. The proportion of deaths from various cancers, crude mortality rates, and standardized mortality rates were calculated. The Joinpoint Regression Program was used to calculate mortality trends and the periodic percentage change (PPC) in these rates. We found that the mortality rate of cancer was 142.15/105; the age-standardized mortality rate using the Chinese standard population in 2000 (ASMRC) and Segi’s world population (ASMRW) were 86.49/105 and 85.73/105 in 2020, respectively. From 1973 to 2020, during the four time periods, the leading five cancer types contributing to the mortality rate among Inner Mongolia residents in 2020 were stomach cancer, esophageal cancer, liver cancer, cervix/uterine cancer, and lung cancer. The four periods of time PYLL ‰ were 9.05‰, 10.79‰, 12.1‰, and 10.38‰ from 1973 to 2020. The overall trend of the crude mortality rate of cancer in Inner Mongolia from 1973 to 2020 increased (PPC =1.77%, P<0.05). Also, the crude mortality rate and ASMRC were higher in men than in women (P<0.05). The mortality rates of cancer in Inner Mongolia increased with age ie first time period and in 2020 for ages 10 to 84. The same trend was observed for ages 0 and 74 in the second and the third time periods. Overall, in 2020, the CMR and the ASMRW in Inner Mongolia were lower than the national level and significantly lower than those in other domestic Chinese provinces. Lung cancer was the most reported cancer. Cancers from the first to seventh place ranking were consistent with the national ranking in 2020. The overall crude mortality rate of cancer in Inner Mongolia during the four periods revealed an increasing trend, and liver cancer-related mortality also showed an upward trend during the four periods. The findings may provide baseline data for cancer research.